Perancangan Penguat Daya L-Band Menggunakan Transistor GaAs p-HEMT MMG15241H Berbasis Mikrostrip - Rifki Amiruddin; Budi Syihabuddin; Yuyu Wahyu (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
The power amplifier which is designed by using BJT (Bipolar Junction Transistor) has a larger power consumption, hence in this research, the FET GaAs p-HEMT MMG15241H is used. The power amplifier designed in this research uses microstrip-based and works at the middle frequency of 1.27 GHz. This research yielded a power amplifier which works at the bandwidth with a range frequency of 1.265 - 1.275 GHz, a gain result of 20.02 dB, and input return loss result of -24.45 dB.